Analysis of Personal Values and Work Culture of Sundanese and Javanese Employees (Case Study of Employees in West Java) - Assyofa, Allya Roosallyn; Rohandi, Moch. Malik Akbar; Frendika, Rusman (KnE Social Sciences, 2024)
West Java has a quite dense population, 65% of the population in West Java are Sundanese. In addition, there are also other tribes, namely the Javanese, which are also found in many areas in West Java. This study aims to analyze differences in employees’ personal values and work cultures based on Sundanese and Javanese ethnicity in West Java. The determination of the two tribes is because most of the population in West Java Province are Sundanese and Javanese. The specific objectives of this study are to analyze the differences between Sundanese and Javanese employees in 1) the hedonistic values, 2) the value of empathy, 3) the value of self-actualization, 4) the integrity, 5) professionalism, 6) satisfaction, and 7) exemplary. The data analysis technique used in this study was descriptive and two-sample independent nonparametric test with the Mann-Whitney, Kolmogorov Smirnov, and Run Woldfowitz tests, using the SPSS version 25. Sample analysis was carried out using criteria consisting of 75 employees of private sector companies using questionnaires in West Java, including Bandung, Purwakarta, Karawang, Subang, and Cianjur. The output of this study indicates that Sundanese and Javanese employees in West Java have different but equally good personal values and work cultures. The personal values consist of 3 main dimensions – namely hedonism, empathy, and self-actualization, while the work culture consists of integrity, professionalism, satisfaction, and exemplary. The most significant difference is shown in the dimension of integrity where the Sundanese show adherence to company rules, while the Javanese are more honest at work. Keywords: Ethnicity; personal values; work culture